Reframing evidence-based practice curricula to facilitate engagement in nursing students - Disler, Rebecca T.; White, Haidee; Franklin, Natasha; Armari, Elizabeth; Jackson, Debra (Nurse education in practice, 2019)
Evidence-based practice underscores a modern approach to nursing to ensure delivery of safe, up-to-date and person-centred care in the evolving clinical environment. While most entry-to-practice nursing courses incorporate elements of evidence-based research curricula, nursing students commonly struggle to see the relevance of research in their training. This study sought to understand nursing students' satisfaction and perspectives on research after an undergraduate research subject was redesigned to make overt the connection between research and professional nursing practice. Satisfaction significantly improved on routinely collected satisfaction surveys over a one-year period (mean increase 0.57, 95% CI 0.40–0.77, P < 0.001; medium effect size, 0.64). Open-ended questions elicited five themes: change to preconceived ideas of research to something accessible and useful; clear link between research and clinical and professional nursing practice; comments on subject format and scaffolded learning; increased skills in effective searching and extracting evidence; and improvements for the future. Student satisfaction increased when the connection between research learning and professional practice was made overt in a core research subject. This approach, along with scaffolded activities to increase confidence, had a marked positive impact on student's attitude and understanding of the utility of evidence-based practice and confidence in scrutinising practice in the clinical environment. •Evidence-based practice underpins nursing to ensure the delivery of safe, up-to-date and person-centred care.•Nursing curriculum incoporates evidence-based research but students often struggle to understand the relevance of research.•Making the relationship between research and clinical practice overt to students increases their overall satisfaction.•Scaffolded and progressive learning activities to increase research skills are useful in improving student understanding.•Improving understanding between evidence and clinical practice increases student confidence in questioning clinical practice.